Dealing with a Porcelain Aorta during Coronary Artery Bypass Grafting. (24th December 2014) - Adesanya, T. M. Ayodele; Kilic, Ahmet
Abstract : We report a complex case of multivessel CAD in a patient with a porcelain aorta and high-grade left subclavian artery stenosis. Utilizing a staged left subclavian artery stent placement with a next-day plan for a four-vessel, on-pump CABG and ascending aortic replacement, this case highlights an organized approach to diagnosing and dealing with a heavily calcified aorta while describing a stepwise algorithm to deal with aortic calcifications prior to initiating cardiac surgery.